Effects of Therapeutic Regimen Adherence Enhancing Strategies on Exacerbations Among Persons with Chronic Obstructive Pulmonary Disease - วงศ์สวัสดิ์ พรสรวง; ชัยอาจ จินดารัตน์; ภิญโญคำ นิตยา (Nursing Journal CMU, 2017)
Persons with chronic obstructive pulmonary disease should adhere to a therapeutic regimen for effective control of exacerbations. This experimental research aimed to examine the effects of therapeutic regimen adherence enhancing strategies on exacerbations among persons with chronic obstructive pulmonary disease. The subjects of the study were persons with chronic obstructive pulmonary disease attending the chronic obstructive pulmonary disease department and the outpatient patient department, Thasala Hospital, Nakhonsrithamaraj Province from March to June 2014. Sixty-four subjects were purposively selected by pair matching technique and divided into a control and an experimental group, with 32 in each group. Research instruments consisted of, 1) the demographic data record form, 2) the therapeutic regimen adherence interview questions form for persons with chronic obstructive pulmonary disease, 3) therapeutic regimen adherence enhancing strategies plan for persons with chronic obstructive pulmonary disease, 4) the educational hand book for persons with chronic obstructive pulmonary disease, 5) the adherence monitoring recording form for researcher and 6) the adherence self-recording form for persons with chronic obstructive pulmonary disease. Data were analyzed by using descriptive statistics, and the Mann-Whitney U-test. Research results revealed that: The mean number of exacerbations among persons with chronic obstructive pulmonary disease who received therapeutic regimen adherence enhancing strategies were statistical significantly lower than those who did not (p < .05). Results of this study demonstrated that therapeutic regimen adherence enhancing strategies can decrease the frequency of exacerbations among persons with chronic obstructive pulmonary disease. These strategies can be used to improve the quality of nursing care for this population.